A state-of-the-art study of cloud manufacturing - Hatema, Noor; Yusof, Yusri; Zuhra A. Kadir, Aini; M A, Mohammed (International Journal of Engineering and Technology, 2018)
There is a considerable industrial standard transfer. This will drive to the adaptable usage of various globally shared, emerging within the manufacturing field by Combining advanced manufacturing models such as the Internet of things, cloud computing, service-oriented technologies, big data, and recently Cloud Manufacturing. Cloud manufacturing a program is a combined program that empowers manufacturers to distribute sources contribute manufacturing services and including supports compatible cooperation. Economically significantources, such as the manufacture of software tools, importance, knowledge, and manufacturing capacity, and material, then become available to supposed users on a global basis, the principal benefits and difficulties of achieving cloud manufacturing are analyzed. the key New technologies for manufacturing model, is cloud manufacturing, cloud manufacturing aims to achieve full participation, free of charge, And easy for utilization of various sources and manufacturing abilities in the form of manufacturing setting. This paper contributes an overview of the cloud manufacturing.Â Â